Effects of tear film after conjunctival autograft transplant and limbal conjunctival autograft transplant for primary pterygium - Wei Wang (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
AIM: To compare the effects of tear film after conjunctival autograft transplant(CAT)and limbal conjunctival autograft transplant(LCAT)for primary pterygium.METHODS: In a prospective study, 150 patients(150 eyes)diagnosed with primary pterygium were collected in Beijing road medical area of Xinjiang Military Region General Hospital from September 2018 to May 2019. The 150 patients enrolled in the study in turn, and divided into two groups by the odd and even number. The odd number underwent CAT and the even number underwent LCAT. Respectively before surgery and 1, 3, 6mo and 1a after surgery, tear film break-up time(TBUT), SchirmerⅠtest(SⅠt)and ocular surface disease index(OSDI)were checked. The date were compared and analyzed.RESULTS:Totally 129 patients(129 eyes)completed the follow-up of 1a, including 64 patients(64 eyes)from the CAT group and 65 patients(65 eyes)from the LCAT group. Four patients(4 eyes, recurrence rate 6.2%)in the CAT group and 3 patients(3 eyes, recurrence rate 4.6%)in the LCAT group developed recurrence. However, there was no significant in recurrence rate between CAT group and LCAT group(P=0.718). There were significant differences between before surgery and after surgery in each group(P<0.05), and there were significant differences between 1mo after surgery and 3, 6mo and 1a after surgery in each group(P<0.05), while there was no significant different among 3, 6mo and 1a after surgery in each group in TBUT, SⅠt and OSDI(P>0.05). Also there was no significant different between CAT group and LACT group in each time in TBUT, SⅠt and OSDI(P>0.05).CONCLUSION:Both CAT and LCAT could effectively treat primary pterygium with low and similar recurrence rate, and the degree of improvement of tear film after primary pterygium operation is similar between the two surgical methods.